KONFLIK KEWENANGAN DALAM PENGELOLAAN HUTAN PESISIR TINJAUAN HUKUM KEHUTANAN - Hertha Frederika Septory (Masalah-Masalah Hukum, 2014)
This research find that mangrove forest are the forest and coastal resourcesso beregulated in Law Number 41 on 1999 and Law Number27 on 2007. According to the principle of lexspecialis derogatlegi lex generalis and lexpos teriori derogatlegi lex priorithat management authority forest owned by the Ministryof Forestry should be interpreted back out side coastal areas which becomes its authority the Ministry of Maritime Affairs and Fisheries